MyHalal: an interactive application - Wong Xin Ying; Zarul Fitri Zaaba (Bulletin of Electrical Engineering and Informatics, 2022)
According to the Halal industry development corporation (HDC). Malaysia’s Halal industry market value is expected to achieve approximately RM614.36 billion by 2025. It indicates that the Halal industry has great potential in covering local and international markets. In Malaysia, the department of islamic development malaysia (JAKIM) is the official agency responsible for Islamic affairs. In most circumstances, the public can check the Halal status of products by accessing the official website. The searching via the website is quite tedious and complex. Therefore, this work bridges the gap by proposing a mobile application namely MyHalal (MH) as a proof of concept which significantly improved the current method. This application will assist users in verifying the Halal status of food products and premises. In this context, MH also introduces a barcode scanner to check the product listing in JAKIM with camera access. Besides that, users also can report an issue when they found any misconduct regarding Halal certification. This mobile application is developed together with the web-based application as the backbone for the administrator to manage technical matters. It is expected to be a user-friendly platform for the users and a channel for JAKIM to manage information and spread awareness about Halal.